Clinical application of the activity index to parameter for evaluation of electromyographic activity of the masticatory muscles - Takashi Tanaka (Dental Journal (Majalah Kedokteran Gigi), 2006)
The purpose of this study was to evaluate the relationship between the intended direction of clenching and changes in the applied activity index of the masticatory muscles. The subjects consisted of twelve male volunteers (average age of 26.3 years). The surface electromyographic activities of the anterior and posterior parts of the temporal muscles, the deep posterior part of the masseter muscle and the superficial central part of the masseter muscle were recorded during the intended clenching in vertical, anterior and posterior directions. The changes of the applied activity index (the relative different value between the examined muscle activity and the superficial central part of the masseter muscle activity) were evaluated. The applied activity indexes of the anterior and posterior parts of the temporal muscles and the deep posterior part of the masseter muscle decreased significantly during the intended clenching in the posterior direction. Those of the anterior and posterior parts of the temporal muscles increased significantly during the intended clenching in the anterior direction. Each applied activity index changed corresponding to the differences of the running directions in the sagittal plane between the superficial masseter muscle and these three muscles. The applied activity indexes of the anterior and posterior parts of the temporal muscles and the deep posterior part of the masseter muscle significantly changed during clenching in anteroposterior direction. Therefore, it was suggested that the applied activity indexes of these three muscles could be used as a parameter to indicate the anteroposterior direction of force on the lower jaw.